Applying Second Language Acquisition Research Findings to Materials: A cognitive-interactionist perspective - Freeborn, Lani (Beyond Words, 2015)
In recent years, ELT publishers have been criticised for not incorporating the findings of second language acquisition (SLA) research into the design of their teaching materials. The first aim of this article is to inform teachers of key research findings from the cognitive-interactionist approach to SLA by discussing five environmental ingredients that contribute to optimal L2 learning. The second aim of this article is to demonstrate how these research findings can be practically applied to the selection and adaptation of teaching materials. It is the author’s hope that teachers will be encouraged to apply this knowledge to their teaching contexts, and be motivated to keep themselves informed of SLA research findings. Keywords: materials development, SLA research, cognitive-interactionism